2019
DOI: 10.1088/1367-2630/ab5a06
|View full text |Cite
|
Sign up to set email alerts
|

Tuning non-Gilbert-type damping in FeGa films on MgO(001) via oblique deposition

Abstract: The ability to tailor the damping factor is essential for spintronic and spin-torque applications. Here, we report an approach to manipulate the damping factor of FeGa/MgO(001) films by oblique deposition. Owing to the defects at the surface or interface in thin films, two-magnon scattering (TMS) acts as a non-Gilbert damping mechanism in magnetization relaxation. In this work, the contribution of TMS was characterized by in-plane angular dependent ferromagnetic resonance. It is demonstrated that the intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These two studies both excluded the TMS contributions. The anisotropy of magnetic damping has been also observed in some epitaxial magnetic alloy lms, such as Co 2 FeAl [17][18][19], Co 2 FeSi [20], Co 2 MnSi [21] and FeGa [22], although whether the origin of the damping anisotropy is intrinsic or extrinsic remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…These two studies both excluded the TMS contributions. The anisotropy of magnetic damping has been also observed in some epitaxial magnetic alloy lms, such as Co 2 FeAl [17][18][19], Co 2 FeSi [20], Co 2 MnSi [21] and FeGa [22], although whether the origin of the damping anisotropy is intrinsic or extrinsic remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research demonstrated that the FM damping can be modulated by tuning the interfacial spin–orbit coupling and TMS effect. , However, these works suffered from high-operation voltage (>400 V) and high energy consumption, limiting their potential applications in the future. , Transitioning from the discussion of polarized light-controlled magnetism, it is important to highlight the superiority of photovoltaic (PV) control. It operates with lower power consumption and minimal thermal impact.…”
Section: Development Of Optical Controllable Magnetism Devicesmentioning
confidence: 99%
“…Recently, several groups [15][16][17][18][19][20][21] reported anisotropic damping in the film plane, i.e., α could be tuned via rotating the magnetization orientation of the FM layer in the same sample. Meanwhile, the anisotropic damping is found to be accompanied with prominent in-plane magnetic anisotropies in the FM layer, e.g., twofold uniaxial magnetic anisotropy (UMA), fourfold magneto-crystalline anisotropy (MCA), or both of them.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic magnetic damping has also been observed in some other magnetic alloy films, such as Co 2 FeAl, [18] Co 2 FeSi, [19] Co 2 MnSi, [20] and FeGa. [21] However, in all these studies, the FM layers are either single-crystalline or highly textured polycrystalline. Since MCA can be completely ruled out, amorphous FM film (e.g., CoFeB) has been found to exhibit a pure in-plane UMA after being deposited on an appropriate substrate (e.g., GaAs).…”
Section: Introductionmentioning
confidence: 99%